2019
DOI: 10.22603/ssrr.2018-0020
|View full text |Cite
|
Sign up to set email alerts
|

Dash-Associated Spondylolysis Hypothesis

Abstract: 1Purpose: In past biomechanical studies, repetitive motion of lumbar extension, rotation, 2 or a combination of both, frequently seen in batting or pitching practice in baseball, 3 shooting practice in soccer, and spiking practice in volleyball, have been considered 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…First, wearing of a hard brace could not fully protect the patient against the mechanical load generated by activities of daily living, such as running or cycling. Goto et al 17) recently reported that sprinting increases the hip extension angle, spine rotation angle, and hip flexion moment, and can be a risk factor for LS. Furthermore, our patient was a Japanese elementary school student, and so the load generated by carrying the traditional heavy Japanese school backpack ( randoseru ) every day might have caused mechanical stress on the lumbar spine.…”
Section: Discussionmentioning
confidence: 99%
“…First, wearing of a hard brace could not fully protect the patient against the mechanical load generated by activities of daily living, such as running or cycling. Goto et al 17) recently reported that sprinting increases the hip extension angle, spine rotation angle, and hip flexion moment, and can be a risk factor for LS. Furthermore, our patient was a Japanese elementary school student, and so the load generated by carrying the traditional heavy Japanese school backpack ( randoseru ) every day might have caused mechanical stress on the lumbar spine.…”
Section: Discussionmentioning
confidence: 99%